Tradition, morality and community: elaborating Orthodox identity in Putin's Russia. Issue 1 (2nd January 2017) - Agadjanian, Alexander
ABSTRACT: This paper draws upon a number of official, semi-official and other public texts related to the current views of the Russian Church on social and political issues. Overall, in spite of a variety of opinions and nuances, a certain mainstream becomes apparent, as expressed through this body of texts. The most discussed topics include moral values related to the human body (such as abortion, euthanasia, reproductive technologies and sexuality) and issues such as blasphemy, juvenile courts and new technologies of personal registration for Russian citizens. 'Traditional morality' has become the signature discourse of the Russian Orthodox Church which is attempting to construct 'tradition' by drawing upon a partly imagined ethos of imperial Russia and the late Soviet Union. Traditional family values are central to the church's rhetoric. The authors of these texts see a presumed decay of traditional values as the main danger that must be opposed. They usually trace the source of this danger directly to the contemporary West. By contrast, they see Russia as a protective shield against these global influences. Either consciously or involuntarily, they translate their religious language of traditional morality into a political rhetoric of solidarity and patriotism. Such ideological rhetoric has direct political implications and analogies in the agenda of Putin's regime. This Russian appeal to 'traditional values', both religious and political, has recently acquired an extraordinary international relevance.